ANTIBACTERIAL ACTIVITY OF TEA, BREADFRUIT, AND PIPER BETLE LEAVES EXTRACTS AGAINST Propionibacterium acnes AND ITS APPLICATION AS ANTI-ACNE MASK - Angie Lucita; Tensiska Tensiska (Jurnal Penelitian Pascapanen Pertanian, 2021)
Tea, breadfruit, and piper betle leaves contain bioactive components that have a function as an antibacterial. The purpose of this study was to determine the type of leaf extract that has the highest inhibition power against Proponibacterium acnes and determine the concentration of the selected extract for mask applications that have good physical characteristics and acceptable to panelists. Extraction of tea, breadfruit, and piper betel leaves were carried out with 96% ethanol solvent using maceration method for 24 hours and concentrated with a rotary evaporator. Thick extracts contribute to antibacterial activity by disk diffusion method and total phenolic content. The selected extract was formulated into a clay mask with concentration of 0.5%, 1%, and 1.5%. The result showed that breadfruit leaf extract had the highest inhibition power against Propionibacterium acnes which was 10.844 ± 0.327 mm (strong inhibition category) so that extract can be applied to clay mask. Breadfruit leaf extract concentration of 1.5% was the chosen formulation because it meets the standards, approved by the panelists and the most effective antibacterial for acne problems.